Farnesoid X receptor: a master regulator of hepatic triglyceride and glucose homeostasis - Jiao Yang; Lu Yan; Li Xiao-ying (Acta Pharmacologica Sinica; Vol 36, No 1 (January 2015): Acta Pharmacologica Sinica(Special Feature:Nuclear Receptors: Biology, Structures, and Drug Discovery）, 2017)
Non-alcoholic fatty liver disease (NAFLD) is characterized by the aberrant accumulation of triglycerides in hepatocytes in the absence of significant alcohol consumption, viral infection or other specific causes of liver disease. NAFLD has become a burgeoning health problem both worldwide and in China, but its pathogenesis remains poorly understood. Farnesoid X receptor (FXR), a member of the nuclear receptor (NR) superfamily, has been demonstrated to be the primary sensor for endogenous bile acids, and play a crucial role in hepatic triglyceride homeostasis. Deciphering the synergistic contributions of FXR to triglyceride metabolism is critical for discovering therapeutic agents in the treatment of NAFLD and hypertriglyceridemia.